2012
DOI: 10.3233/wor-2012-0268-949
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ergonomics in design processes: a case study within an engineering consultancy firm

Abstract: This paper reports on a case study within an engineering consultancy firm, where engineering designers and ergonomists were working together on the design of a new hospital sterile processing plant. The objective of the paper is to gain a better understanding of the premises for integrating ergonomics into engineering design processes and how different factors either promote or limit the integration. Based on a grounded theory approach a model illustrating these factors is developed and different hypotheses ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…It was also not clear from other studies in the literature what "ideal" HF integration in design processes would look like. Much of the HF literature discusses HF requirements (Wulf et al, 1999), or sign-off as integration (Waterson and Kolose, 2010), and in some cases direct participation with designers (Seims and Sorensen and Broberg, 2012). The indicators in this study included adaptation of industrial engineering tools with HF metrics and inclusion in several stages of the design process, requirements that engineers be accountable for the metrics, sign-off by the HFS, and training for engineers in compliance with the HF metrics.…”
Section: Determine the Indicators Of Hf Integration In The Design Processmentioning
confidence: 99%
“…It was also not clear from other studies in the literature what "ideal" HF integration in design processes would look like. Much of the HF literature discusses HF requirements (Wulf et al, 1999), or sign-off as integration (Waterson and Kolose, 2010), and in some cases direct participation with designers (Seims and Sorensen and Broberg, 2012). The indicators in this study included adaptation of industrial engineering tools with HF metrics and inclusion in several stages of the design process, requirements that engineers be accountable for the metrics, sign-off by the HFS, and training for engineers in compliance with the HF metrics.…”
Section: Determine the Indicators Of Hf Integration In The Design Processmentioning
confidence: 99%
“…As observed in the calender machine example, equipment lists are often replicated from one project to another without updating. Nevertheless, the revision of this document must occur in each new project, both in partnership with other disciplines, and according to the specifics of the future work.As each design stage involves new decisionmaking, at different levels, the accumulation of knowledge about the real work -through the role of the ergonomist -must be considered at all these stages[18][19][20]. Furthermore, it is suggested that both cognitive work and organizational dimension be further researched, to take it into the projects' context.The limits imposed on this work, including the availability of places onboard for analysis in reference situations, should be considered.…”
mentioning
confidence: 99%